1997
DOI: 10.1073/pnas.94.13.7088
|View full text |Cite
|
Sign up to set email alerts
|

A novel subviral agent associated with a geminivirus: The first report of a DNA satellite

Abstract: Numerous plant RNA viruses have associated with them satellite (sat) RNAs that have little or no nucleotide sequence similarity to either the viral or host genomes but are completely dependent on the helper virus for replication. We report here on the discovery of a 682-nt circular DNA satellite associated with tomato leaf curl geminivirus (TLCV) infection in northern Australia. This is the first demonstration that satellite molecules are not limited to RNA viral systems. The DNA satellite (TLCV sat-DNA) is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
129
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 27 publications
2
129
0
1
Order By: Relevance
“…Sequence comparison shows that this region aligns with that part of the ToLCV sat-DNA (Dry et al, 1997) containing an inverted repeat flanking a sequence that is identical to the ToLCV iteron. Mutagenesis and protein binding assays have demonstrated that this motif in both ToLCV and sat-DNA represents a high affinity Rep binding site, although it is not required for replication of either the begomovirus or its satellite (Lin et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sequence comparison shows that this region aligns with that part of the ToLCV sat-DNA (Dry et al, 1997) containing an inverted repeat flanking a sequence that is identical to the ToLCV iteron. Mutagenesis and protein binding assays have demonstrated that this motif in both ToLCV and sat-DNA represents a high affinity Rep binding site, although it is not required for replication of either the begomovirus or its satellite (Lin et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Li et al (2007) recently demonstrated that approximately the 386 nt upstream of the stem-loop structure in ToLCV sat-DNA, as well as the stem-loop structure itself, are essential for replication. This includes the predicted stem-loop structure encompassing the ToLCV iteron described above (Dry et al, 1997;Lin et al, 2003). Hence, in many respects, the DNA-b replication origin resembles the multiple domains of bipartite begomoviruses (Argüello-Astorga et al, 1994;Argüello-Astorga & Ruiz-Medrano, 2001), although the specificity of Rep recognition seems more relaxed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a) was produced representing deletions in all regions of the sat-DNA except for a 77 nt region (nt 641 through nt 682 to nt 35) flanking stem-loop I, which contains the conserved nonanucleotide sequence TAATATTAC essential for sat-DNA replication (Dry et al, 1997). These sat-DNA deletion constructs were co-agroinoculated, with TLCV, into whole plants (six) or leaf strips of N. benthamiana as described previously (Dry et al, 1997;Rigden et al, 1996). Fig.…”
mentioning
confidence: 99%